Unmet nursing care needs on medical and surgical wards: A scoping review of patients' perspectives. Issue 3 (25th November 2019) - Bagnasco, Annamaria; Dasso, Nicoletta; Rossi, Silvia; Galanti, Carolina; Varone, Gloria; Catania, Gianluca; Zanini, Milko; Aleo, Giuseppe; Watson, Roger; Hayter, Mark; Sasso, Loredana
Abstract: Aims and objectives: To review and synthesise research studies on surgical and medical inpatients' perceptions on unmet nursing care needs. Background: Missed nursing care is a growing phenomenon that has been shown to adversely affect care outcomes—mainly in adult medical and surgical care settings. However, to date the aggregated and synthesised evidence of missed care comes from research that measures perceptions on missed care in surgical and medical settings from nurses, but not from the patients. Design: Scoping review. Methods: In September 2018, three databases were searched: MEDLINE/PubMed, CINAHL and SCOPUS and papers were selected using the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses guidelines. Inclusion criteria were as follows: primary studies; published in peer‐reviewed journals; in English or Italian; and regarding routine care provided to adult inpatients. Quality appraisal and a thematic analysis were conducted. Results: Of the 1541 abstracts initially identified, 44 papers were included. Five themes emerged: "communication, " "self‐management, autonomy and education, " "personal sphere, " "essential physical care" and "emotional and psychological care." The majority of the unmet needs were related to the "personal sphere" and "emotional and psychological care." These unmet needs were not identified in previous literature on nurses' perspectives of missed care. Also, physical care deficits like oral hygiene were identified. Conclusion: It is important to take into account patients' perspectives. The themes focusing on patients' personal sphere, and emotional and psychological care, underline how patients need nurses to pay more attention to their cultural background, consider the person as a whole and for nursing care to be holistic and respectful of patients' dignity. Relevance to Clinical Practice: This study intends to raise awareness amongst nurses and policymakers about the importance of addressing missed nursing care and unmet patients' needs in adult medical or surgical inpatient settings to ensure high‐quality care and patient satisfaction.